'Don't panic people! Trump will tweet the virus away': memes contesting and confirming populist political leaders during the COVID-19 crisis. Issue 16 (10th December 2021) - Nørgaard Kristensen, Nete; Mortensen, Mette
ABSTRACT: When the COVID-19 pandemic triggered a global health crisis in early 2020, memes of populist political leaders were disseminated in abundance on social media. At first sight, these political memes satirized and exposed the hazardous actions, appearances and communicative strategies of the populist leaders in this unforeseen situation that not only unsettled existing power balances, but also standard modes of professional and personal conduct. Based on a thematic analysis of memes of British Prime Minister Boris Johnson and US President Donald Trump during the COVID-19 crisis, this paper finds, however, that the political memes' critical and affirmative power conflated. This challenged their potential as counter-narratives to the actions and communication of these populist leaders. We argue that this can be explained by an overlap in the communicative form of populism and memes: Political memes are a social media genre that uses incongruent humor to expose the contradictions, conflicts and hypocrisy of populist politicians. Similarly, populist politicians communicate in polarizing and personalizing rhetoric that emphasizes conflicts and the mischiefs of others on social media and beyond. This raises the broader question of how populist leaders might be criticized and their actions subjected to scrutiny in political memes without feeding into their own communicative patterns and logics, and thus unintentionally confirming their worldview and interpretations of events.